1992
DOI: 10.1101/gad.6.3.367
|View full text |Cite
|
Sign up to set email alerts
|

The scalloped gene encodes a novel, evolutionarily conserved transcription factor required for sensory organ differentiation in Drosophila.

Abstract: The scalloped {sd) gene of Drosophila melanogaster was initially characterized by mutants affecting structures on the wing of the adult fly. The sequence of a cDNA clone of the gene reveals a predicted protein sequence homologous to that of a human transcriptional enhancer factor, TEF-1 (68% identity). The homology includes a sequence motif, the TEA domain, that was shown previously to be a DNA-binding domain of TEF-1. An sd enhancer trap strain expresses the reporter gene in a subset of neuroblasts in the cen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
144
0

Year Published

1993
1993
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 177 publications
(151 citation statements)
references
References 58 publications
7
144
0
Order By: Relevance
“…We also tested the muscle-specific expression of two different well-characterized reporter constructs that express ␤-galactosidase (␤-gal) under the control of sd enhancers. sd ETX4 animals have an enhancer-trap (␤-gal) P-element construct inserted into the 5Ј regulatory region of the sd locus and have been used extensively to obtain the pattern of sd expression in embryo and other tissues (Campbell et al, 1992;Deshpande et al, 1997;Varadarajan and VijayRaghavan, 1999;Muller et al, 2005). Similar to what we observe with FISH detection of the sd signal, in sd ETX4 embryos, significant levels of ␤-gal can be detected in some muscle cells (Figure 2A).…”
supporting
confidence: 68%
See 2 more Smart Citations
“…We also tested the muscle-specific expression of two different well-characterized reporter constructs that express ␤-galactosidase (␤-gal) under the control of sd enhancers. sd ETX4 animals have an enhancer-trap (␤-gal) P-element construct inserted into the 5Ј regulatory region of the sd locus and have been used extensively to obtain the pattern of sd expression in embryo and other tissues (Campbell et al, 1992;Deshpande et al, 1997;Varadarajan and VijayRaghavan, 1999;Muller et al, 2005). Similar to what we observe with FISH detection of the sd signal, in sd ETX4 embryos, significant levels of ␤-gal can be detected in some muscle cells (Figure 2A).…”
supporting
confidence: 68%
“…Sd is the only member of the Transcriptional Enhancer Factor-1 (TEF-1) family of proteins in Drosophila (Campbell et al, 1992) and together with an activating cofactor, Vg, induce formation of the wing. In fact, ectopic expression of Vg, in the cells of the developing eye that also express Sd, leads to a respecification of these cells to a wing phenotype (Halder et al, 1998;Simmonds et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…11 The vg-GAL4 strain that drives GAL4 expression according to part of the vgBEenhancer was provided by M Hoffmann and S Morimura. The vgBE-lacZ strain that drives b-galactosidase expression according to the vgBE enhancer was described in Williams et al 8 The sd ETX4 strain is a sd-LacZ enhancer trap described in Campbell et al 13 The E2F rm729 line, which contains an enhancer trap inserted in the dE2F1 gene, is called E2F-lacZ in this study. 22 The E2F 91 mutation is described as a null allele for the gene.…”
Section: Drosophila Strains and Mediummentioning
confidence: 99%
“…[10][11][12] vg and sd are coexpressed in the wing imaginal disc and dimerization of VG and SD seems to be a prerequisite for translocation of the dimer to the nucleus, where it acts as a functional transcription factor. [12][13][14] In fact, in the heterodimer, SD contains the transcription enhancer activator (TEA) DNA binding domain, while VG provides the transcriptional activation domain. 10,12,14 It has been shown that ectopic expression of vg in other imaginal discs induces wing outgrowths, this being dependent on the presence of SD.…”
Section: Introductionmentioning
confidence: 99%